Heliodorus and the Assassination of Seleucus IV according to Dan 11:20 and 2 Macc 3 - Scolnic, B. (Journal of Ancient Judaism, 2016)
The impetus for the assassination of Seleucus IV in 175 B. C. E. is commonly associated with his robbing the temples and oppressing the peoples of the Seleucid kingdom in order to pay tribute to Rome according to the Treaty of Apamea. Reconsideration of the relevant evidence – especially Dan 11:20 and 2 Macc 3, with attention to a passage from Appian, inscriptions from Delos, the Heliodorus stele and the Ptolemaios dossier – suggests another explanation for these events. If Seleucus robbed the temples to finance his “royal splendor,” it is possible that Heliodorus and others tasked with taxing the kingdom may have objected to his controversial policies and taken action against him because of them. © 2016 [2017] Vandenhoeck & Ruprecht GmbH & Co. KG, Göttingen
Keywords: dept.jst

When did the future Antiochos iv arrive in Athens? - Scolnic, B. (Hesperia, 2014)
The mention of an Antiochos in an Athenian inscription, I 7453, which dates to 178/7 b.c., has led scholars to accept that the future Antiochos IV lived in Athens from 178 to 175, and was not just present in the city in 175, as a statement by Appian seems to indicate. A reevaluation of the evidence calls into question both this extended sojourn and the identification of the Antiochos in the inscription, inviting us to reconsider the circumstances and the chronology of events surrounding the accession of Antiochos IV. © The American School of Classical Studies at Athens.
Keywords: dept.jst

Ἀντίπατρος ἀδελφιδοῦς: Was Antipatros son of Epigonos of Telmessos the “Nephew” of Antiochos III? - Scolnic, B. (Dialogues d'Histoire Ancienne, 2022)
Keywords: dept.jst; peer-reviewed

The failure of Poseidon, 'Averter of Disaster' and the mythical geography of Isaiah 23:1-14 - Scolnic, B. (Acta Antiqua Academiae Scientiarum Hungaricae, 2024)
The nostos, the return home in Greek mythology, is most often a journey over the sea, and it is the god Poseidon who rules the sea, both ensuring the safe passage of fishermen and sailors and causing disasters to individuals like Ajax son of Oileus, sometimes through obstacles like his daughter Charybdis. Most famously, he uses his power to hinder the nostos of Odysseus, all the while knowing he cannot prevent him from reaching home. This example illustrates how a god who may once have been the most powerful deity can no longer control ultimate results. As his power declines over the centuries, that of Zeus increases. It is also by sea that we see the ships in Isaiah 23, attempting to return to their homes in Sidon and Tyre on the eastern Mediterranean coast. In this Biblical passage from the eighth century BCE, the ships wail when they see that their seaport homes have been destroyed; there are no homes to which they can return. The great god of the Sea and the epichoric gods have failed to protect the cities which are considered their progeny. The Israelite prophet mocks their powerlessness and celebrates the power of his One God. There is no nostos, no homecoming for ships because they no longer have homes. Just as Poseidon could not prevent Odysseus from his nostos, the so-called Averter of Disaster has not prevented the disaster that has befallen his children. © 2023 Akadémiai Kiadó, Budapest.
Keywords: Biblical-Mythological Inter-Connections; Odyssey; Poseidon; dept.jst; nostos; peer-reviewed